Introduction of Folk Physical Culture Traditions in the Educational Process of Senior Preschool Children - Anatolii Volchynskyi; Yaroslav Smal; Olexandr Malimon; Andrii Kovalchuk (Lesya Ukrainka Volyn National University, 2017)
The article analyzes the feasibility of national physical culture in the educational process in preschool educational establishments, historic significance and especially the use of traditional physical training in the physical and mental development of senior preschool children. The extensive experience of many national and foreign researchers and listed priorities for their implementation were overviewed. The fundamental basis of education and training is a concern for the health of the younger generation, because first of all teachers have task to choose the most appropriate means of education and training of preschool children to improve their physical development and state of health. Widespread use of elements of Ukrainian traditions in preschool educational establishments is an important mean of spiritual and physical strength, self-knowledge and recreation. Every nation, depending on the social and economic conditions of its development, psychological structure, ideology and geographic location, long historical time created distinctive types of exercise, outdoor games, amusements, entertainment, improved methods for their use, which then also became a kind of folk physical culture.